Attenuated Systemic Microvascular Function in Men with Coronary Artery Disease is Associated with Angina but not Explained by Atherosclerosis. (12th October 2013) - Strain, W. David; Hughes, Alun D.; Mayet, Jamil; Wright, Andrew R.; Kooner, Jaspal; Chaturvedi, Nish; Shore, Angela C.
Abstract Introduction Refractory angina is the occurrence of clinical symptoms despite maximal therapy. We investigated associations between microvascular function, atherosclerotic burden, and clinical symptoms in subjects with CAD. Methods Skin microvascular response to heating and ischemia was assessed in 167 male volunteers by laser Doppler fluximetry; 82 with CAD on maximal therapy and 85 with no known CAD (noCAD). CAC scores, carotid IMT, and femoral IMT were measured and symptoms were scored using the Rose angina questionnaire. Results Patients with CAD had poorer microvascular response to heating (114[95% CI 106–122]au CAD vs. 143[134–153]au no CAD; p < 0.0001) and ischemia (42[38–46]au CAD vs. 53[78–58]au. noCAD; p = 0.001). Thirty‐eight percent of the noCAD group had elevated CAC scores. There were no associations between markers of atherosclerosis and microvascular function. Forty‐two percent of the CAD group had refractory angina. This was associated with impaired microvascular function compared to those with elevated CAC scores but no symptoms (109 [95–124]au vs. 131[122–140]au; p = 0.008). Conclusions Men with symptomatic CAD have poorer microvascular function compared to individuals without CAD. Microvascular function does not correlate with atherosclerosis, but is impaired in individuals with refractory angina. Microvascular dysfunction may play a role in the symptomatology of angina.